Management of Marriage Guidance Programs in Enhancing The Readiness of Prospective Brides and Grooms - Intan Juliani Hutasuhut; Ahmad Tamrin Sikumbang (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Purpose − The Marriage Guidance Program (Bimbingan Perkawinan/Bimwin) is a strategic initiative of the Ministry of Religious Affairs to enhance the readiness of prospective couples in building resilient families. The effectiveness of this program is closely related to the quality of management at the implementation level, particularly within the Office of Religious Affairs (Kantor Urusan Agama/KUA). This study aims to analyze the management of the Marriage Guidance Program at KUA Batang Kuis by examining planning, implementation, and evaluation functions, as well as identifying supporting and inhibiting factors. Method − A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. Informants were purposively selected, including the Head of KUA, religious counselors, and program participants. Findings − The findings indicate that program planning and implementation have referred to official regulations and guidelines issued by the Ministry of Religious Affairs. However, program evaluation remains predominantly administrative and has not fully adopted an outcome-based approach. Supporting factors include the availability of official guidelines and facilitator competence, while inhibiting factors involve participants’ time constraints and limited evaluation mechanisms. This study provides practical recommendations for strengthening the management of the Marriage Guidance Program at the KUA level to enhance its contextual adaptability.